BMP4 dose dictates lineage specification bias in human periodontal ligament stem cells - Li, Yihong; Tang, Qinghuang; Li, Liwen; Lin, Chensheng; Guo, Minhui; Zhang, Yanding; Yan, Fuhua; Lin, Minkui (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionPeriodontal ligament stem cells (PDLSCs) represent a promising therapeutic cell source for regenerating periodontal tissues impaired by disease. While exogenous BMP4 has been used to induce human PDLSC differentiation into distinct periodontal cell lineages, its dose-dependent effects on lineage specification remain poorly understood.MethodsHere, we systematically investigated how BMP4 dosage modulates human PDLSC differentiation toward osteogenic and tenogenic lineages using single-cell RNA sequencing and in vitro functional assays.ResultsSingle-cell transcriptomic analysis revealed that endogenous BMP4 expression inversely correlated with RUNX2 but positively correlated with SCX within PDLSC subpopulations. Pseudotemporal analysis demonstrated biphasic differentiation dynamics: low BMP4 expression corresponded to high expression of both markers, while BMP4 upregulation inversely correlated with RUNX2 but positively correlated with SCX. In vitro validation confirmed dose-dependent effects: low-dose BMP4 (10 ng/mL) sustained multipotency by upregulating both RUNX2 and SCX, while high-dose BMP4 (100 ng/mL) promoted tenogenic differentiation and suppressed osteogenic commitment. BMP4 overexpression induced nuclear SCX accumulation, confirming its pivotal role in tenogenic lineage commitment. Mechanistically, osteogenic differentiation required both BMPR1A and BMPR1B receptors, whereas tenogenic differentiation depended exclusively on BMPR1B signaling.ConclusionThese findings demonstrate that precise BMP4 dosage regulation dictates PDLSC differentiation outcomes, providing crucial insights for optimizing PDLSC-based periodontal regenerative therapies.